2022
DOI: 10.1097/txd.0000000000001300
|View full text |Cite
|
Sign up to set email alerts
|

Public Understandings of the Definition and Determination of Death: A Scoping Review

Abstract: Background. Advances in medicine and technology that have made it possible to support, repair, or replace failing organs challenge commonly held notions of life and death. The objective of this review is to develop a comprehensive description of the current understandings of the public regarding the meaning/definition and determination of death. Methods. This scoping review was conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
(348 reference statements)
1
8
0
Order By: Relevance
“…Our data, as others’, 8 , 9 , 11 15 , 19 reveal that many FMs struggle with the difference between brain death and coma, and some continue to struggle with this differentiation years after the death of their loved one. Despite several decades of research on this topic, many FMs, and the public continue to be confused about the differences between brain death and other neurologic disorders such as comas or persistent vegetative state.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our data, as others’, 8 , 9 , 11 15 , 19 reveal that many FMs struggle with the difference between brain death and coma, and some continue to struggle with this differentiation years after the death of their loved one. Despite several decades of research on this topic, many FMs, and the public continue to be confused about the differences between brain death and other neurologic disorders such as comas or persistent vegetative state.…”
Section: Discussionsupporting
confidence: 66%
“…Despite several decades of research on this topic, many FMs, and the public continue to be confused about the differences between brain death and other neurologic disorders such as comas or persistent vegetative state. 8 , 11 , 19 , 29 – 32 We have found that the timing and frequency of conversations with families are important for their comprehension. Families need to be informed early in the death determination process, and need to have information repeated several times to understand.…”
Section: Discussionmentioning
confidence: 99%
“… 17 A scoping review has evaluated the general public’s understanding of the definition and determination of death globally. 18 Nevertheless, multiple knowledge gaps persist regarding families’ perspectives about their relative’s death. Qualitative studies about families’ experiences and perceptions of WLSM, DCC, and DNC processes are key elements of knowledge to gather concerning end-of-life and organ donation.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Then consider the work about the public’s understanding of the definition and determination of death. There is a 2022 scoping review (11), a 2023 national survey of public opinion in Canada (12), and a 2023 report of interviews in family members with relatives dying after determination of DNC (13). Despite these detailed articles on families at the time of death, we have heard little about physicians and their decision-making when families refuse testing for the determination of DNC (14).…”
Section: What Is To Be Learned From Refusals To Allow Examination For...mentioning
confidence: 99%